Lysophosphatidylinositol: a novel link between ABC transporters and G-protein-coupled receptors - Ruban, Emily L.; Ferro, Riccardo; Ahmad Arifin, Syamsul; Falasca, Marco (Portland Press Ltd., 2014)
Lysophosphatidylinositol (LPI) is a well-known bioactive lipid that is able to activate signalling cascades relevant to cell proliferation, migration, survival and tumorigenesis. Our previous work suggested that LPI is involved in cancer progression since it can be released in the medium of Ras-transformed fibroblasts and can function as an autocrine modulator of cell growth. Different research groups have established that LPI is the specific and functional ligand for G-protein-coupled receptor 55 (GPR55) and that this GPR55–LPI axis is able to activate signalling cascades that are relevant for different cell functions. Work in our laboratory has recently unravelled an autocrine loop, by which LPI synthesized by cytosolic phospholipase A2 (cPLA2) is pumped out of the cell by ATP-binding cassette (ABC) transporter C1 (ABCC1)/multidrug resistance protein 1 (MRP1), initiating a signalling cascade downstream of GPR55. Our current work suggests that blockade of this pathway may represent a novel strategy to inhibit cancer cell proliferation.